VARIASI DIKSI PENGGAMBARAN SOSOK IBU DALAM LIRIK LAGU-LAGU BERTEMAKAN IBU DI INDONESIA (KAJIAN SEMANTIS) - Muhammad Adib Fanani; Hari Windu Asrini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the variations in diction used to depict the figure of a mother in Indonesian song lyrics themed around mothers through a semantic approach. The background lies in the close relationship between language, culture, and identity, where diction serves not only as a communication tool but also reflects social values and the sacred role of mothers, encompassing boundless love, selfless sacrifice, and moral strength. However, representations of mothers in song lyrics are often homogeneous, leading to issues such as reinforcing gender biases and mismatches with the evolving roles of women in modern society. The objective is to describe the form, functioins, and meanings of these diction variations. Employing a qualitative descriptive analytic method, data were sourced from Indonesian songs from the 1970s to the 2020s, such as Ibu by Nasida Ria, Ibu Ibu Ibu by Pidi Baiq, Keramat by Rhoma Irama, Muara Kasih Bunda by Erie Suzan, Doa Ibu by Armada, Ibu by Iwan Fals, Pesona Potretmu by Ada Band, Bunda by Melly Goeslaw, Terima Kasih by Jayadi, Ibu by Haddad Alwi feat Farhan, Ibu Aku Ingin Bersandar by Nabila Maharani, Mama Kaulah Bintang by Romaria, Nyanyian Rindu untuk Ibu by Ebiet G. Ade, Bertaut by Nadin Amizah. The analysis is based on Gorys Keraf’s diction theory and Abdul Chaer’s semantics, with data collection techniques involving documentation and note taking, validated throught triangulation. Results indicate that forms of diction variations cover physical aspects (such as biological sacrifices), psychological emotional aspects (such as care and deep bonds), and social aspects (such as religious hierarchies). Their functions act as symbols of love, narrative drivers, an moral theme reinforcers, while meanings include fields of affection with sacred components, synonym and metaphor relationships, and connotative spiritual shifts. The conclusion asserts that these diction variations are not merely artistic but serve as ideological tools for maternalism, reflecting Indonesia’s cultural values. With implications for literary and semantic studies. Future research is recommended to compare with international song lyrics for a comparative perspective.